2008
DOI: 10.1007/s11270-008-9850-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of MSW Source-Classified Collection on Polycyclic Aromatic Hydrocarbons in Residues from Full-Scale Incineration in China

Abstract: Municipal solid waste (MSW) sourceclassified collection represents an advancement in resource recycling and secondary pollution control in China. Comparative experiments were performed to assess the effect of a newly-established MSW source-classified collection system on polycyclic aromatic hydrocarbons (PAHs) in bottom ash from an incinerator (BA), fly ash from a boiler (FAB) and fly ash from a bag filter (FABF) of a full-scale MSW incinerator in China. Compared with FAB or FABF, PAHs were mainly concentrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 46 publications
(75 reference statements)
2
14
0
Order By: Relevance
“…Thus a particular attention should be paid to PAHs when bottom ash is reused or landfilled. When compared with other incineration plants, the PAH levels were consistent with those from one MSW plant in Hangzhou, China, with the range of 1961.0-2420.2 g/kg [11]. Compared with the data from other countries (Table 4), total PAH concentrations in this study were in the similar range as those found in Orebro, Sweden (480-3590 g/kg) [8,9], while were higher than those in Roma, Vernaison and London [7,10,27].…”
Section: Total 16 Pahs In Mswi Bottom Ashsupporting
confidence: 67%
See 2 more Smart Citations
“…Thus a particular attention should be paid to PAHs when bottom ash is reused or landfilled. When compared with other incineration plants, the PAH levels were consistent with those from one MSW plant in Hangzhou, China, with the range of 1961.0-2420.2 g/kg [11]. Compared with the data from other countries (Table 4), total PAH concentrations in this study were in the similar range as those found in Orebro, Sweden (480-3590 g/kg) [8,9], while were higher than those in Roma, Vernaison and London [7,10,27].…”
Section: Total 16 Pahs In Mswi Bottom Ashsupporting
confidence: 67%
“…In the described protocol, the surrogate standard was used to quantify 16 target compounds. The operating parameters of the ion trap mass spectrometry (ITMS) system were set as follows: electron impact at 70 eV, scan rate at 0.5 s, RF storage level at 45 u, axial modulation at 4.5 V, ion source temperature at 200 • C, transfer line temperature at 280 • C, manifold temperature at 50 • C, 50 A for the filament emission current, electron multiplier voltage at 1650 kV and resonant mode for collision-induced dissociation (CID) [11,24]. The 16 PAHs considered as primary environmental concern to USEPA were naphthalene, acenaphthylene, acenaphthene, fluorene, phenanthrene, anthracene, fluoranthene, pyrene, benz [ …”
Section: Pah Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Incineration process involves conversion of elemental constituents in organic waste to toxic gases and non-toxic gases (4) . Control of combustion conditions alters the composition of the various secondary substances resulting from the incineration process.…”
Section: Introductionmentioning
confidence: 99%
“…Fly ash, the by-product generated from MSW incineration (Shi et. al., 2008;Shi et al, 2009), also belongs largely to the CaO-CaCl 2 -CaSO 4 -Al 2 O 3 -SiO 2 system, Yao et al (1999) have reported the synthesis of tobermorite from MSW incinerator fly ash by hydrothermal treatment in the presence of NaOH solution at 180°C. Chemical composition analysis sets forth SiO 2 , CaO, and Al 2 O 3 being the major waste-insoluble components of MSW incinerator fly ash, which is hence a suitable starting material for tobermorite synthesis.…”
Section: Introductionmentioning
confidence: 99%